Rancang Bangun Rangka (Chasis) Mobil - Alfian Muhajrin; Nirwanpaliki; Ricaldin; Saddang; Sudarsono; Prinop Askar (Program Pendidikan Vokasi Teknik Mesin, 2023)
An electric car is a car that is driven by an electric motor and uses electrical energy stored in a battery. The use of electric cars is considered effective in addition to not causing air pollution and simpler engine construction. In the use of electric cars, of course, requires a frame that functions as a support for all the loads on the vehicle. A frame construction itself must have strength, light weight and have flexibility value. In the design of the frame (chassis) of electric cars has a purpose, namely the shape of the frame design (chassis) of electric cars and the strength of the frame (chassis) of electric cars with the bending test method. In the use of frame construction used type of ladder frame (H), for the frame material itself using non-ferrous metal materials, namely Aluminium. In the connection process, a drilling process is used for keeling nails, from the design of the frame (chassis) of an electric car with a length of 223.5 cm, front width of 47.5cm, middle and rear width 33 cm and frame weight 24.40 kg. The bending testing process here uses 2 driver loads of 45 kg and 82 kg. Measurements are carried out through the balance point on the frame that has been obtained, so that the bending test obtained a deflection value of 0.3 cm with a driver weight of 45 kg and 0.6 cm with a driver weight of 82 kg, In the position before the load is given and after the load is given the deflection back in the initial position of 15.4 cm. Thus, the frame (chassis) of an electric car has met the requirements of the vehicle frame, which has a value of flexibility or flexibility and is light and strong.